Small extracellular vesicles secreted from senescent cells promote cancer cell proliferation through EphA2 - Masaki Takasugi (Nature Portfolio, 2017)
Although senescent cell secretome can promote the growth of surrounding cancer cells, the role of extracellular vesicles in this process has not been well understood. Here the authors show that ROS increase the sorting of EphA2 into extracellular vesicles in senescent cells, which promotes proliferation of cancer cells.